A severity comparison of leukoaraiosis in ischemic and hemorrhagic stroke: a retrospective study - Søfteland, Bendik; Leto, Nedim; Næss, Halvor (Frontiers in Neurology, 2024)
Introduction: Leukoaraiosis (LA) is a common neuroradiological finding in patients suffering from stroke. Cerebral small vessel disease (SVD) is one of the leading etiologies behind both ischemic and hemorrhagic stroke (ICH), and for development of LA. Significant evidence that LA predicts risk of functional dependency and mortality, exists. However, studies examining the difference in LA severity between ischemic and hemorrhagic stroke is lacking. We therefore aimed to compare severity and abundance of LA in the two stroke subgroups.Methods: All patients admitted to the Department of Neurology, Haukeland University Hospital with an ischemic stroke and intracerebral hemorrhagic stroke (ICH) diagnose in the period 2006-2020 were included. We collected patient data regarding risk factors, clinical, radiological findings and outcomes from our local stroke registry. The presence and severity of LA were assessed using the Fazekas score based on CT imaging. We evaluated outcome using the modified Rankin Score (mRS) 7 days post stroke.Results: A total of 5084 patients were included in our analyses, 4437 (87 %) with ischemic stroke and 647 (13%) with ICH. LA was present in 2476 (45%) patients. In our ordinal logistic regression model, adjusting for age, sex, known hypertension, known diabetes mellitus and smoking, LA was more severe and more abundant in ICH compared to ischemic stroke patients (Fazekas score 1; OR Følsomhet Intern (gul)1.54, Fazekas score 2; OR 1.88 and Fazekas score 3; OR 2.13; p<0.001). Increasing severity of LA was associated with worse functional outcomes in both groups (ischemic stroke OR 1.49; p<0.001 and ICH OR 1.36; p<0.025.In this study, LA was more severe and abundant in patients with ICH.Unadjusted analyses showed that the association between ICH and LA increased by LA severity